Social Media for Wildlife Conservation Campaign in South Sumatra, Indonesia - Ardhika, Ryan Difa; Santoso, Anang Dwi; Elfandari, Safitri (Jurnal Kawistara, 2025)
This study examines how the South Sumatra Natural Resources Conservation Agency and the Belantara Foundation utilise Instagram to deliver messages about wildlife conservation. A total of 470 Instagram posts published by these organisations throughout 2022 were analysed using quantitative content analysis. The findings show that the South Sumatra BKSDA tends to focus on posts related to field actions and the current status of wildlife, while the Belantara Foundation emphasises educational content and community engagement. The analysis reveals differences in how each institution frames conservation messages and visual strategies to communicate with the public. Rather than measuring impact, this study highlights the distinctive approaches used by government and non-government institutions in using social media to convey conservation issues. The findings contribute to understanding how message design and media framing can support public engagement in conservation communication.